2017
DOI: 10.1002/pd.5164
|View full text |Cite|
|
Sign up to set email alerts
|

Roadmap for an early gene therapy for cystic fibrosis airway disease

Abstract: Gene therapy provides a mutation-independent approach to treat or even cure CF airway disease. To develop a clinical candidate for CF gene therapy, a thorough examination of preclinical efficacy in relevant cell and animal models is a prerequisite. For a long time, the CF field was struggling with a lack of appropriate animal models for CF airway pathology. Since 2008, many different and complementary animal models have been generated that develop hallmarks of CF airway disease, including the CF pig, ferret, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 145 publications
(264 reference statements)
0
18
0
2
Order By: Relevance
“…In search for a cure for CF, several gene therapy approaches have been explored 5 , mostly based on CFTR cDNA gene addition through viral or non-viral vectors 6,7 . Despite promising results obtained in the respiratory tract of animal models 810 and advancements in gene therapy clinical trials 1114 , curative goals were hampered mainly by low expression levels of the delivered CFTR .…”
Section: Introductionmentioning
confidence: 99%
“…In search for a cure for CF, several gene therapy approaches have been explored 5 , mostly based on CFTR cDNA gene addition through viral or non-viral vectors 6,7 . Despite promising results obtained in the respiratory tract of animal models 810 and advancements in gene therapy clinical trials 1114 , curative goals were hampered mainly by low expression levels of the delivered CFTR .…”
Section: Introductionmentioning
confidence: 99%
“…The greatest obstacle to clinical success is the efficacy of gene delivery ( Carlon et al, 2017 ). There are many approaches to improve this aspect, but viral and non-viral vectors are the most used vectors to carry nucleic acids into the cells.…”
Section: Beyond Ivacaftor and Lumacaftor New Hopes From Gene Therapymentioning
confidence: 99%
“…Recently, the UK CF Gene Therapy Consortium (GTC) has completed a double-blinded, placebo-controlled multi-dose phase IIb trial with 12 years or older age patients with moderate or mild lung disease. This trial has demonstrated that gene delivery was well-tolerated but benefit of liposome delivery was modest ( Carlon et al, 2017 ).…”
Section: Beyond Ivacaftor and Lumacaftor New Hopes From Gene Therapymentioning
confidence: 99%
“…It is unclear whether appropriate research ethics approvals and parental consent were available. We do hope that this reckless “Wild West” behaviour will not put a brake on appropriately done gene therapy research, as this form of therapy may bring significant progress, especially in the field of fertility treatment, hematologic disorders (thalassemia and sickle cell disease) as well as for other genetic conditions, including cystic fibrosis …”
Section: Introductionmentioning
confidence: 99%